Low birth weight babies in Sitiawan, Perak - Rural Health Survey 1997 - Ab Sallam, Atiya (Faculty of Medicine, University of Malaya, 1999)
The single most important determinant of newborn survival and future growth is the birth weight of the infant. According to the World Health Organisation (WHO),low birth weight contributes to an estimated 9.1 million infant deaths which occur each year. ( l) it not only contributed to about 13.5% of all births at the maternity hospital in Kuala Lumpur but also to 74.8% of all deaths in 1985.